How interior design responds to neurodiversity: implementing wearable technologies in neurodesign processes - Kwon, Jain; Linihan, Suzie; Iedema, Alyssa; Schmidt, Alea; Luo, Chenyi; Marrufo, Karime (Frontiers in Built Environment, 2023)
This perspective article, looking through the lens of neurodiversity, discusses the benefits and challenges of implementing virtual environments and wearable technologies in interior design and related fields. While the relationship between human perception and built environments has long been studied in the environmental design disciplines, the direct impact on occupant performance related to neurodiversity has been underexplored in research, with a shortage of knowledge supporting how it can be applied in design practice concerning the end users. Individuals’ perceptual, cognitive, and affective responses to their surroundings vary, as neurodiversity plays a key role in the invisible, human-environment interaction. Thus, measuring, analyzing, and understanding affective, perceptual, and cognitive experiences is a challenging process in which various factors come into play, and no single method or measurement can adequately work for all. Due to such challenges, research has also utilized various biometric measurements and tools for immersive experiments in physical and virtual environments, e.g., eye tracking used in studies on gaze behaviors and immersive virtual reality (IVR) used in studies on the spatial perception of dementia patients. Along with empirical methods, studies have stressed the contribution of phenomenology to looking into the hidden dimension, the ‘why factors’ of perception, cognition, and affectivity. Concerning the methodological approach, this perspective article shares insights into a novel process model, Participatory Neurodesign (PND) framework, used in wayfinding research and design processes utilizing eye tracking and IVR. Opportunities for neurodesign research and design practice are also discussed, focused on the health, safety, and well-being of end-users.